2018
DOI: 10.1101/302323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D Functional Ultrasound Imaging of Pigeons

Abstract: Highlights-We describe a novel ultrafast functional ultrasound technique (HDfUS) -HDfUS offers continuous recording with unmatched spatiotemporal resolution -HDfUS allows to resolve complex 4D neurovascular responses in the brain -First fUS study on non-mammalian species AbstractRecent advances in ultrasound Doppler imaging have allowed to visualize brain activity in small mammalian species such as rats and mice. In birds, this type of functional ultrasound imaging was impossible up to now because birds have p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Since its introduction in 2011 17 , fUS has been used to image neural activity during epileptic seizures 17 , olfactory stimuli 21 , and behavioral tasks in freely moving rodents 22,23 . It has also been applied to many non-rodent species including ferrets 24 , pigeons 25 , non-human primates (NHPs) 26 , and humans [27][28][29] . Unlike functional magnetic resonance imaging (fMRI), fUS can be applied in freely moving subjects using miniature, head-mountable transducers.…”
Section: Mainmentioning
confidence: 99%
“…Since its introduction in 2011 17 , fUS has been used to image neural activity during epileptic seizures 17 , olfactory stimuli 21 , and behavioral tasks in freely moving rodents 22,23 . It has also been applied to many non-rodent species including ferrets 24 , pigeons 25 , non-human primates (NHPs) 26 , and humans [27][28][29] . Unlike functional magnetic resonance imaging (fMRI), fUS can be applied in freely moving subjects using miniature, head-mountable transducers.…”
Section: Mainmentioning
confidence: 99%
“…Functional ultrasound (fUS) has recently emerged as an efficient alternative to BOLD fMRI for functional brain mapping, with millisecond time and mesoscopic (∼100 × 100 × 200 μm) spatial resolution 9,10 . It has been used to investigate olfactory 5,11,12 , visual 13,14 , and somatosensory 9,15,16 responses in anesthetized and awake rodents, and applied to ferrets 17 , pigeons 18 , monkeys 19 and humans 20,21 . In the mouse olfactory bulb (OB), we have recently shown that global fUS sensory responses are tightly correlated to odor 22 .…”
mentioning
confidence: 99%
“…This means that the deep cortical folds of the visual cortex within the calcarine sulcus are inaccessible to these techniques (27,28). New functional ultrasound (fUS) imaging techniques have recently been found to provide high spatiotemporal resolution (100 μm, 1 Hz) even in deep structures (up to 1.5 cm) (29,30), and have been applied to three-dimensional (3D) mapping of the visual system of rodents and pigeons (4,29,31). The technique measures changes in the cerebral blood volume (CBV) within microvessels using ultrafast Doppler (32), combined with spatiotemporal clutter filtering based on singularvalue decomposition (33).…”
mentioning
confidence: 99%